Comparative Study of the Quality Factors of Two Different Cultivars of Pepper (Piper nigrum L.)-Karimunda and Panniyur-I - Sobhana, D.; Abhilasha, A.; Cyril, Wilma; Suresh Kumar, B. (Asian Journal of Chemistry, 2010)
Pepper is known for centuries for its taste and flavour and aptly called the king of spices. There are hundred cultivars of black pepper cultivated in various parts of Kerala. In the present study, we compare the quality factors of two different cultivars of Piper nigrum L.- Karimunda and Panniyur-I. The moisture and volatile oil content of both fresh and dry pepper samples and refractive index of the volatile oils was determined. Marked differences in chemical composition of volatile oils from fresh and dry pepper was noticed. The percentage of monoterpenes and sesquiterpenes varied in the two cultivars. The fresh peppery note of the Karimunda can be correlated with the higher content of volatile constituents. Knowledge of the variation in the composition of pepper oils from different cultivars is essential when pepper is used as a component of food flavourings.